Community-Dwelling Older Adults' Adherence to Environmental Fall Prevention Recommendations. (June 2019) - Taylor, Suzänne F.; Coogle, Constance L.; Cotter, James J.; Welleford, E. Ayn; Copolillo, Al
This study examined the impact of personalized versus generalized education about environmental fall prevention recommendations on older adults' adherence with recommendations. Secondary aims focused on the impact of recent falls and perceived susceptibility of future falls on adherence with recommendations. Twenty-four community-dwelling older adults aged 65 to 89 years were randomized into two groups to receive either personalized or generalized education intervention on environmental fall prevention recommendations. A significant difference was found in the mean total percentage of adherence with recommendations of those receiving personalized education (69%) compared with those receiving generalized education (37%). No statistically significant relationship was found between sustaining recent falls, nor perceived susceptibility to future falls, and their extent of adherence with environmental fall prevention recommendations. Providing personalized education for environmental fall prevention recommendations may improve older adults' adherence with the recommendations given.